Testy sekwencyjne dla parametrów rozkładu normalnego lewostronnie uciętego - Pekasiewicz, Dorota (The Sequential Tests for Parameters of Left-Truncated Normal Distribution, 2007)
The sequential probability ratio tests, presented in this paper, are used to verify hypotheses about parameters μ and ϭ of density function of the left-truncated normal distribution N(μ,ϭ). The statistic of the first presented test is the likelihood functions ratio, calculated under the assumption that respectively: alternative and null hypotheses are true. In the case of the independent sample sampling scheme, likelihood function is a product of density functions of the normal truncated distribution. In the second test, the statistic is based on the pseudo-likelihood functions ratio with density functions of the normal distribution N(μ,ϭ). Apart from theoretical considerations, the results of simulation analysis of the properties of both sequential tests are presented in the paper. Estimated numerical characteristics of the sample sizes, necessary to take a decision about the acceptance of one of the verified hypotheses, allow to compare regarded tests in respect to their efficiencies.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1163, s. 230-245